2007
DOI: 10.1177/0748233707081906
|View full text |Cite
|
Sign up to set email alerts
|

ATSDR evaluation of potential for human exposure to tungsten

Abstract: As part of its mandate, the Agency for Toxic Substances and Disease Registry prepares toxicological profiles on hazardous chemicals found at Comprehensive Environmental Response, Compensation and Liability Act, National Priorities List sites that have the greatest public health impact. These profiles comprehensively summarize toxicological and environmental information. This article constitutes the release of portions of the Toxicological Profile for Tungsten. The primary purpose of this article is to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Tungsten is commonly used in metal alloys (e.g., cemented carbide) and in numerous tools, automotive parts, and other products. The widespread use of tungsten alloys makes low-level occupational exposure common, but it usually involves coexposure with other metals ( 30 ). Environmental exposure to tungsten also occurs commonly through water, food, and ambient air.…”
Section: Discussionmentioning
confidence: 99%
“…Tungsten is commonly used in metal alloys (e.g., cemented carbide) and in numerous tools, automotive parts, and other products. The widespread use of tungsten alloys makes low-level occupational exposure common, but it usually involves coexposure with other metals ( 30 ). Environmental exposure to tungsten also occurs commonly through water, food, and ambient air.…”
Section: Discussionmentioning
confidence: 99%
“…Agarwal et al [ 50 ] also reported a significant positive association between cardiovascular and cerebrovascular disease and tungsten which was selected as a main effect as well as interaction with lead in AENET-I and as the fourth most important variable in BART. Tungsten, commonly used in metal alloys [ 59 ], has also been positively associated with diabetes [ 60 ] and peripheral artery disease [ 54 ]. Barium, a silvery-white metal used for many different purposes in industry [ 61 ], was also selected in our multipollutant models.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin B mediates direct NLRP3 oligomerization or ROS formation via mitochondrial membrane disruption (5). ROS in turn facilitates the dissociation of TXNIP from its inhibitor TRX (6). Newly dissociated TXNIP, binds to inactive NLRP3 (7) resulting in NLRP3 activation and subsequent oligomerization (8) which activates caspase-1 (9).…”
Section: Discussionmentioning
confidence: 99%
“…Further, increased use of tungsten may potentially contaminate surrounding air, water, and soil near tungsten mines and industrial sites. 6 Tungsten has been identified at several hazardous waste sites that have been proposed for inclusion on the environmental protection agency's (EPA) national priority list. 4 Regulatory agencies from various countries (USA, Australia, Sweden, New Zealand, China) have issued regulatory guidelines with respect to tungsten exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation